The Standard Portfolio Choice Problem in Germany - Christoph Breunig; Steffen Huck; Tobias Schmidt; Georg Weizsäcker (The Economic Journal, 2021)
We study an investment experiment with a representative sample of German households. Respondents invest in a safe asset and a risky asset whose return is tied to the German stock market. Experimental investments correlate with beliefs about stock market returns and exhibit desirable external validity at least in one respect: they predict real-life stock market participation. But many households are unresponsive to an exogenous increase in the risky asset's return. The data analysis and a series of additional laboratory experiments suggest that task complexity decreases the responsiveness to incentives. Modifying the safe asset's return has a larger effect on behaviour than modifying the risky asset's return.
Keywords: D1; D14; D84; G11; 300; stock market expectations; stock market participation; portfolio choice; financial literacy; complexity